PENGARUH DISIPLIN KELUARGA TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA KELAS XI SMA NEGERI 1 SIPOHOLON TAHUN AJARAN 2021/2022 - Ida Susyanti Panjaitan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
ABSTRACT, The purpose of this study was to find out whether there was a positive and significant effect of family discipline on the learning achievement of PAK Class XI students of SMA Negeri 1 Sipoholon Academic Year 2021/2022. The research population was all Class XI students of SMA Negeri 1 Sipoholon for the 2021/2022 Academic Year who were Protestant Christians, namely 360 people. The sample is the entire population, namely 30 people. The research data were analyzed in the following steps: 1) Test the analysis requirements by: a) Test the relationship, it is known that rcount > rtable or 0.5096 > 0.361. This shows that there is a relationship between family discipline and PAK learning achievement of class XI students of SMA Negeri 1 Sipoholon, b) The significant test of the relationship shows that the value of tcount > ttable is 10.384 > 2.048. From the results of the significance test of the relationship it can be concluded that there is a positive and significant relationship between family discipline and PAK learning achievement of Class XI students of SMA Negeri 1 Sipoholon, 2) Effect test: a) The magnitude of the influence of family discipline on PAK learning achievement of Class XI students of SMA Negeri 1 Sipoholon is: (r2) x 100% = 0.2597 x 100% = 25.97%, b) Testing the regression equation Y over X, the regression equation Yˆ = 29.85+0.62X means that it is in a constant state of 29.85, so PAK learning achievement of students will increase 0.62 times from the value of family discipline, c) the value of Fcount = 9.77 > Ftable (0.05,1.28) = 2.01, then the research hypothesis is accepted.